PENERAPAN MODEL LEARNING CYCLE 5E BERBANTUAN LKPD UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI ZAT ADITIF - Khofifah Indar Parawangsa; Mohammad Budiyanto (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research aimed to describe: (1) the implementation of learning, (2) increase in concept understanding, and (3) the student responses to the application of the learning cycle 5E model on additive substances. This research used a pre-experimental design with one group pretest posttest design. Participants in this research were 16 students of class VIII A UPT SMP Negeri 14 Gresik. Data collection techniques were conducted by observation, pretest and posttest, and questionnaires. Data analysis of the implementation of learning conducted by calculating the average of each learning activity. Increase in concept understanding was analyzed with the N-Gain test. The students’ responses were analyzed by calculating the average percentage of student responses. The implementation of learning obtained high results with very good category in the first meeting and the second meeting. The concept understanding increased in posttest scores and N-Gain scores obtained results in medium category. The results of the student responses got a high percentage which meant that students responded very well. Based on the result, it can be concluded that the application of the learning cycle 5E model assisted by worksheet could improve student concept understanding on additive substances.